Analysis of the productivity of the retail sector of the Republic of Serbia regarding the COVID-19 pandemic - Marić, Radenko; Vukmirović, Goran; Džever, Sanja; Macura, Nikola (Anali Ekonomskog fakulteta u Subotici, 2023)
The sector that has suffered through the highest market turbulence caused by the COVID-19 pandemic is the retail sector. Evidence for this can be found in the great shocks on the demand side, primarily for essential products necessary in conditions of self-isolation and quarantine. The principal question is whether the sharp increase in demand, restrictions on the operation of retail facilities, strict epidemiological measures among both employees and consumers, tightened safety protocols, mandatory protective equipment, et cetera, have affected the business, primarily of small retailers. In this regard, the aim of the paper is to analyze productivity between key groups of retailers in the market of the Republic of Serbia with special reference to the assessment of productivity in the period before and during the COVID-19 pandemic. The results showed statistically significant differences existed between the productivity of local and regional retail chains in relation to the leading retail chains. It was confirmed that the average productivity of associated retailers is higher than that of independent (local) retailers. Also, there are differences in productivity per employee between the observed groups. However, the results showed no statistically significant difference in the degree of productivity of the retail sector in the period before and during the COVID-19 pandemic. The obtained results suggest that the retail supply chain has stabilized after the first months of the pandemic and has shown its complete flexibility to sudden market shocks. Guidelines for future research are included in the paper.